1993
DOI: 10.1126/science.8484119
|View full text |Cite
|
Sign up to set email alerts
|

Sequences and Structures Required for Recombination Between Virus-Associated RNAs

Abstract: RNA recombination has been described for a number of viruses in the plant and animal kingdoms, but the mechanisms of selection of recombination sites are poorly understood. The nonrandom recombination between two subviral RNAs associated with turnip crinkle virus was used to study the requirement for specific sequences and structures in the generation of recombinant molecules. Single-base mutations that disrupted either the stem or the loop of one of the two computer-predicted stem-loop structures eliminated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
128
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(129 citation statements)
references
References 35 publications
1
128
0
Order By: Relevance
“…Junction sites of homologous recombination are influenced by RNA secondary structure: evidence for similarity-assisted recombination Intermolecular RNA secondary structures such as stemloops have been shown to be important in directing nonhomologous or similarity non-essential recombination sites in TCV, TBSV and cucumoviruses (Carpenter et al, 1995;Cascone et al, 1993;Chare & Holmes, 2006;de Wispelaere et al, 2005;Suzuki et al, 2003;White & Morris, 1994), whereas did not find a clear correlation between RNA secondary structure and homologous recombination sites. However, a high proportion (21 of 27) of independent recombination-junction sites between mutations were found in recombinants formed between X and Bi type CP genes and co-localized to predicted stemloop structures.…”
Section: Recombination Rate and Selection Pressurementioning
confidence: 94%
See 2 more Smart Citations
“…Junction sites of homologous recombination are influenced by RNA secondary structure: evidence for similarity-assisted recombination Intermolecular RNA secondary structures such as stemloops have been shown to be important in directing nonhomologous or similarity non-essential recombination sites in TCV, TBSV and cucumoviruses (Carpenter et al, 1995;Cascone et al, 1993;Chare & Holmes, 2006;de Wispelaere et al, 2005;Suzuki et al, 2003;White & Morris, 1994), whereas did not find a clear correlation between RNA secondary structure and homologous recombination sites. However, a high proportion (21 of 27) of independent recombination-junction sites between mutations were found in recombinants formed between X and Bi type CP genes and co-localized to predicted stemloop structures.…”
Section: Recombination Rate and Selection Pressurementioning
confidence: 94%
“…Considering that the experimental system selected amplification of only movement-competent CP genes and that only products of precise recombination events (no mismatch mutations in proximity to the junction sites) were detected, the results obtained allow classification of the precise recombination into the similarity-assisted group as defined by Nagy & Simon (1997). Another example for similarity-assisted recombination has been given (Cascone et al, 1993; for TCV satellite RNA; however, recombination hot spots were observed to cluster at the base of a hairpin motif. By using this recombination system, it should be possible to reduce successively the sequence similarity of intact genes offered for recombination, in order to analyse the similarity-dependent limits of precise homologous recombination.…”
Section: Recombination Rate and Selection Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…This deletion mechanism does not involve any particular primary sequence, which is also a characteristic of the heteroduplex-mediated recombination mechanism, but contrasts with the recombination mechanism described for TCV (Cascone et al, 1993 ;Simon & Bujarski, 1994 ;Carpenter et al, 1995). The minimum length of double-stranded RNA structure which can promote efficient recombination in BMV was estimated at between 20 and 30 nt (Nagy & Bujarski, 1993).…”
Section: Mutational Analysis Of Defective Interfering (Di)mentioning
confidence: 99%
“…They are also RNA replication enhancers that may promote RNA recombination directly by binding the replicase-aborted nascentstrand complex during the crossover event (Nagy & Simon, 1997;. Stem-loop structures were also observed in recombination sites in TCV (Cascone et al, 1993;Nagy et al, 1999b), tombusviruses (White & Morris, 1995) and norovirus (Nayak et al, 2008). However, a comprehensive study of how these two factors affect plant RNA virus recombination based on whole-genome analyses has not yet been conducted.…”
Section: Introductionmentioning
confidence: 99%